Research update for the immune microenvironment of chronic endometritis. (August 2022) - Zeng, Shuli; Liu, Xinqiong; Liu, Dongzhou; Song, Wencong
Abstract: Chronic endometritis (CE) is a persistent and subtle local inflammatory disease characterized by abnormal plasma cell infiltration in the endometrial stroma.The incidence of chronic endometritis is as high as 15–57.5% in women suffering from infertility, implantation failure of in vitro fertilization (IVF) and unexplained recurrent abortion. Many studies both at home and abroad have shown that CE can reduce the receptivity of endometrium and affect embryo implantation. According to the existing reproductive immunity research, the abnormality of immune cell subsets in endometrium is an important factors leading to pregnancy failure. The immune microenvironment in endometrium consists of immune cells and immune molecules, and their influence on embryo implantation can not be ignored. This review paper discusses the controversy of pathogenesis, diagnosis and treatment of CE from the perspective of immune microenvironment by referring to related literature at home and abroad, and investigates the possible ways to improve the diagnosis and treatment of CE. Highlights: Endometrial lesion or an imbalance of the endometrial immune microenvironment can induce chronic endometritis (CE). We discuss the controversy of pathogenesis, diagnosis and treatment of CE from the view of immune microenvironment. By consulting the relevant literature at home and abroad, this paper discusses the topic of immune microenvironment of CE. New ways for measuring the immunological milieu of endometrium were discussed in order to improve CE diagnosis and treatment.